A phylogenetic revision of the true bug genus Heraeus (Hemiptera: Rhyparochromidae: Myodochini), with the description of two new genera and 30 new species - Dellapé, Pablo Matías (2016)
Prior to this study, the genus HeraeusStål, 1862 included 14 species, all of which are restricted to the Western Hemisphere. Three species are known from the Nearctic Region, nine from the Neotropical Region, and two mainly tropical elements are distributed in both regions. In this contribution, we consider Heraeus cincticornisStål, 1874 a junior synonym of Heraeus elegans (Walker, 1873), select a lectotype for Heraeus coquillettiBarber, 1914, and neotype for Lygaeus triguttatusGuérin-Méneville, 1857, and describe 28 new species. In addition, the two new genera, Baranowskiobiusgen.nov., to include H.elegans (Baranowskiobius eleganscomb.nov.) and two new species, and Paraheraeusgen.nov., to include Heraeus eximiusDistant, 1882 (Paraheraeus eximiuscomb.nov.), are described. Previously described species and new taxa are (re)described and illustrated, including male genitalia. Scanning electron micrographs, general habitus photographs, and distribution maps are included for all species studied. A phylogenetic analysis comprising 46 terminal taxa and 50 morphological characters was performed, and five species groups were hypothesized, including the coquilletti, caliginosus, guttatus, illitus, and plebejus groups. All known species of Heraeus and the new genera are included in the phylogenetic analysis. The type species of the genera MyodochaLatreille, 1807, OrthaeaDallas, 1852, and Paisana Dellapé, 2008 are used as out-groups.